The characterisation and summer distribution of ultraphytoplankton in the Gulf of Gabès (Eastern Mediterranean Sea, Tunisia) by using flow cytometry. (1st February 2015) - Hamdi, I.; Denis, M.; Bellaaj-Zouari, A.; Khemakhem, H.; Bel Hassen, M.; Hamza, A.; Barani, A.; Bezac, C.; Maalej, S.
Abstract: The Gulf of Gabès in the Eastern Mediterranean Basin is one of the largest continental shelves and is a highly productive area. This is in contrast to the Eastern Mediterranean Basin as a whole which is oligotrophic to ultraoligotrophic. Over recent years, due to increased pressure from anthropological activities, there has been a decline in the biological resources in the Gulf of Gabès. This has led scientists to focus their research on the different trophic levels of the food chain and in particular on phytoplankton. Studies dedicated to phytoplankton in the Gulf of Gabès have previously relied on conventional global approaches. This work on the other hand, examines ultraphytoplankton (<10 µm) distribution at the single cell level in different water masses, during a summer cruise (2008). Three distinct water masses were identified: modified Mediterranean waters (MMW), modified Atlantic waters (MAW) and Ionian waters (IW). Despite the summer period, nutrients were abundant and non-limiting. Flow cytometry resolved five cell groups, Prochlorococcus, Synechococcus, picoeukaryotes, nanoeukaryotes and a group of unidentified cells. These cells were characterised by low fluorescence signals and scatter signals larger than that of cyanobacteria and picoeukaryotes and thus were labelled LFNano for low fluorescence nanoeukaryotes. They were found in very high abundances, whereas the other usual groups were relatively low in abundance despite the favourable growth conditions. LFNano found during a 2012 summer cruise in the same area, were also sorted by flow cytometry and observed by scanning electron microscopy. Choanoflagellates were identified, and these nanoflagellates appear to account for the low abundance in the usual ultraphytoplankton group due to their efficient feeding/grazing mechanism. However, the most abundant LFNano could not be identified. Results strongly suggest a top-down control of the ecosystem, consistent with the high productivity of the Gulf that implies a rapid transfer of matter and energy to higher trophic levels. Highlights: Oligotrophic chl a concentration contrasts with high level of living resources. Substrates never exhausted. Abnormally low abundance of cyanobacteria and eukaryotic ultraphytoplancton. Co-presence of a choanoflagellate sp. Top-down controlled ecosystem, quick transfer of production to higher trophic levels.